Attitude and ICT skills as determinants of utilisation of open educational resources by undergraduates in faculty of education, University Of Ilorin, Nigeria - Bashorun, Musediq Tunji; Baruwa, Lukman Oladimeji; Famuyiwa, Shola Temitope; Falabi, Modupeola .O. (Communicate: Journal of Library and Information Science, 2024)
This study investigates the attitude and ICT skills as determinants of utilisation of Open Educational Resources by undergraduates in the Faculty of Education, University of Ilorin, Nigeria. A descriptive survey design was adopted and a sample size of 385 was derived from a population of 10,609. A simple random sampling technique applied and a questionnaire was used to collect data. The statistical analysis used for the study is frequency count, percentages, mean and standard deviation. The findings showed types of OERs as Digital Tutorials, Digital Learning Objects, Open Journals, Open Textbooks, Online Modules, and Open Courseware were commonly available. Respondents developed a positive attitude (mean of above 2.16) towards OERs and possessed high levels of ICT skills, particularly in Microsoft Office, Computer Literacy, and Online OERs Skills, while their skills in Multimedia Applications were rated lower. Also, the findings revealed that OERs have enormous benefits such as improvement of the quality of education, reduce the information access gap, and accelerate knowledge flow. Furthermore, the study revealed challenges such as low awareness of OERs, insufficient recognition of OER repositories and the need for OERs to support local languages and cultural values. The study concluded that undergraduates developed a positive attitude towards the utilisation of OERs despite challenges hindered their optimal usage. Among the recommendations are ICTs training to improve ICT skills particularly in areas where undergraduates are lacking should be organised by university management. In addition, OER content should be developed or adapted to support local languages and cultural contexts to enhance OER relevance and usability.